Study of the taxonomic and functional diversity of the macroinvertebrate assemblages in an Andean mountain river. - Díaz-Rojas, Camila Andrea (2020)
Introduction: The structure, taxonomic diversity and functional diversity of the aquatic macroinvertebrate assemblages are estimators sensitive to variations in the surrounding environment. The physical environment is a key factor, where the substrate and hydraulic dynamics modify the availability of resources, the structuring, the functioning of the community and the ecosystem. Objective: Determine the structure, taxonomic diversity and functional diversity of the macroinvertebrate assemblages under different abiotic conditions in the Hato Laguna river, a tributary of Lake Tota. Methods: 120 biological samples were collected in four sampling events in two reaches in the river. Depth, flow velocity, channel width and roughness of the substrate were measured in situ. The functional traits evaluated were: body length, body shape, type of breathing, type of locomotion, trophic guild and functional feeding groups. Results: A total of 38 taxa were identified; Diptera, Coleoptera and Trichoptera orders presented the highest abundance of families and genera. Orthocladiinae, Andesiops sp. and Simulium sp. were more abundant groups under high-velocity conditions in the upper reaches. Nectopsyche sp. was abundant in the lower sections related to lower velocity and greater channel width. According to the taxonomic diversity indices, variation by reaches and samplings was presented without observing trends. In the upper reaches, the MOPF trophic guild (collectors), in tegument respiration, and small body size were characteristic. In the lower reaches, the assembly was of the scraper type with gill breathing and flattened body shape. The richness, divergence and functional evenness were higher in the upper reaches. In the Canonical Correspondence Analysis, the highest values ​​of width and speed were related to categories attached to the substrate and endobenthic, while low width and roughness were related to the categories of flattened body shape, microphytes food resource, and maximum body size. Conclusions: The system presented a variation in the abiotic conditions, in the structure, taxonomic and functional diversity of the macroinvertebrates. The role of the flow velocity as a determining variable of the structure and function of the community is highlighted. Likewise, functional diversity stands out as an expression of the described traits, which is why it is related in the upper reaches with the dominance of taxa such as Orthocladiinae, Chironominae, Simulium sp. and Andesiops sp.